Optical excitation of a forbidden magnetic resonance mode in a doped lutetium-iron-garnet film via the inverse Faraday effect. - Reid, A; Kimel, A; Kirilyuk, A; Gregg, J; Rasing, T (2010)
The effective magnetic field induced by a femtosecond pulse of circularly polarized light, via the inverse Faraday effect, is shown to excite a magnetic-dipole forbidden exchange spin resonance in a lutetium iron garnet. An external magnetic field cannot excite this mode, as the iron sublattices have the same gyromagnetic ratio and no net torque can be applied between them. However, since the sublattices have different magneto-optical susceptibilities, the inverse Faraday effect induces different effective fields on different iron sites, allowing excitation.